Implementation of Shehu Adomian Decomposition Method upon Fisher's Equation for Analytical Solution - Kapoor, Mamta (Discontinuity, Nonlinearity, and Complexity, 2026)
In present research work, an iterative Shehu Adomian Decomposition Method is implemented to tackle the approximated and exact outcomes of the Fisher's Reaction-Diffusion equation. In present work, the Adomian polynomials are employed to fetch required terms in the process. The robustness and efficiency of the proposed technique are validated using the graphical matching of the outcomes. It can be assured that iterative Shehu ADM is one of the easy-to-implement techniques to tackle complex-natured PDEs. With the aid of the iterative Shehu ADM, a vast range of fractional PDEs can be solved as future research work.